Analysis of Policy Capacity in Bureaucratic Simplification Within the Provincial Government of DKI Jakarta - Wijayanti, Dania; Salomo, Roy (Green Publisher Indonesia, 2025)
This study examines the policy capacity of the DKI Jakarta Provincial Government in implementing the bureaucratic simplification policy, focusing on the transition from structural to functional positions at echelon III and IV levels. Using the Policy Capacity Theory by Wu et al. (2015), this qualitative research evaluates the analytical, operational, and political capacities through interviews and document analysis. The findings indicate that the Jakarta Provincial Government has sufficient analytical capacity supported by competent personnel and regulatory frameworks. However, operational capacity faces challenges such as uneven training and limited budget support. Political capacity is constrained by insufficient socialization and the lack of a clear work system for functional positions. The study concludes that while the policy is supported by adequate capacity, sustainable reform requires stronger political will, system improvements, and harmonization between central and local regulations.